Provision of Registration Services by Public Administration Agencies in the Field of Land Protection - M. V. Chorna (Law and Safety)
The author of the article has stated that the land relations reform and the start of decentralization led to changes in the system of public administration agencies in the field of land protection and expanded their powers, for example, to provide registration services.